From Prediabetes to Type 2 Diabetes Mellitus in Women with Polycystic Ovary Syndrome: Lifestyle and Pharmacological Management - Arianna Pani (International Journal of Endocrinology, 2020)
Aims. Despite the very clear association between polycystic ovary syndrome (PCOS) and dysglycemia, few studies have explored the continuum of glycemic alterations leading from minor glucose abnormalities to overt diabetes. The purpose of this review is to trace the natural history of glycemic alteration in women with PCOS. Methods. We performed a literature review without time limit until August 2019. Inclusion criteria were studies addressing the association between impaired glucose tolerance or impaired fasting glucose or type 2 diabetes (T2D) and PCOS with at least an English abstract. The exclusion criteria were no PCOS or impaired glucose tolerance or impaired fasting glucose or T2D as outcome. The outcomes of interest were the onset of impaired glucose tolerance, impaired fasting glucose, T2D, and the progression from impaired glucose tolerance or impaired fasting glucose to T2D. Results. Healthy diet and physical activity are the first-line therapy for PCOS. Treatment with metformin was associated with significant lower 2-hour postload glucose levels and with reduction in fasting glucose when compared to placebo. Thiazolidinediones were more effective in reducing fasting glucose levels compared to placebo. Metformin and pioglitazone treatments showed similar effects on fasting glucose levels. The sodium-glucose cotransporter-2 inhibitor empagliflozin did not show differences in metabolic parameters when compared to metformin. The combination therapy with metformin plus the glucagon-like peptide-1 receptor agonist liraglutide was associated with significant improvements in basal and postload glucose levels compared with only liraglutide. Likewise, a combination therapy with the dipeptidyl peptidase-4 inhibitor saxagliptin and metformin demonstrated superiority versus metformin in fasting glucose and oral glucose tolerance test normalization. Myo-inositol supplementation was associated with lower insulin levels, glucose levels, and insulin resistance when compared with placebo, metformin, or estrogen treatments. Conclusions. The use of insulin-sensitizing agents, such as metformin and inositols, along with lifestyle interventions may improve the metabolic profile in PCOS women.